Regional Constraints on Soft Law Legitimacy: Some Australian Geopolitical Perspectives. - Herr, Richard (Arctic Portal, 2011)
Dr. Richard Herr, School of Government, University of Tasmania, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.